Artistic features of Uzbek cinematographic art 1940-1960 years - Otajon O‘ktamovich Dostonov (Genius Journals, 2022)
In this scientific article, the artistic features of the Uzbek art of cinematography in 1940-1960 are thoroughly studied. D.Demusky, M.Kransyansky the analysis of the episodes of the film, which portrayed, one staffed episode, the techniques of filming, the style of operation, artistic characteristics through light were also studied.
Keywords: creativity; artistry; a staff; a young operator